Tissue and serum samples of patients with papillary thyroid cancer with and without benign background demonstrate different altered expression of proteins - Abdullah, M.I.; Lee, C.C.; Junit, Sarni Mat; Ng, Khoon Leong; Hashim, Onn Haji (PeerJ, 2016)
Background: Papillary thyroid cancer (PTC) is mainly diagnosed using fine-needle aspiration biopsy. This most common form of well-differentiated thyroid cancer occurs with or without a background of benign thyroid goiter (BTG). Methods: In the present study, a gel-based proteomics analysis was performed to analyse the expression of proteins in tissue and serum samples of PTC patients with (PTCb; n = 6) and without a history of BTG (PTCa; n = 8) relative to patients with BTG (n = 20). This was followed by confirmation of the levels of proteins which showed significant altered abundances of more than two-fold difference (p < 0.01) in the tissue and serum samples of the same subjects using ELISA. Results: The data of our study showed that PTCa and PTCb distinguish themselves from BTG in the types of tissue and serum proteins of altered abundance. While higher levels of alpha-1 antitrypsin (A1AT) and heat shock 70 kDa protein were associated with PTCa, lower levels of A1AT, protein disulfide isomerase and ubiquitinconjugating enzyme E2N seemed apparent in the PTCb. In case of the serum proteins, higher abundances of A1AT and alpha 1-beta glycoprotein were detected in PTCa, while PTCb was associated with enhanced apolipoprotein A-IV and alpha 2-HS glycoprotein (AHSG). The different altered expression of tissue and serum A1AT as well as serum AHSG between PTCa and PTCb patients were also validated by ELISA. Discussion: The distinctive altered abundances of the tissue and serum proteins form preliminary indications that PTCa and PTCb are two distinct cancers of the thyroid that are etiologically and mechanistically different although it is currently not possible to rule out that they may also be due other reasons such as the different stages of the malignant disease. These proteins stand to have a potential use as tissue or serum biomarkers to discriminate the three different thyroid neoplasms although this requires further validation in clinically representative populations.